Modelling of the growth and productivity of soy cultivars under irrigation and rainfed conditions - Barbosa, Wemerson Saulo da Silva; Lyra, Guilherme Bastos; Souza, Ivomberg Dourado Magalhães de; Souza, José Leonaldo de; Teodoro, Iêdo Peroba de Oliveira; Lopes, Joyce Herculano; Santos, José Wanderson Silva dos (Revista de Ciências Agroveterinárias, 2022)
The aim of this study was to evaluate the fit of semi-empirical models for growth and productivity in soya cultivars under irrigation and rainfed conditions in the state of Alagoas. Two experiments were conducted, the first during the dry season from 14/11/18 to 03/04/19 (140 days), and the second during the rainy season from 20/06/19 to 28/10/19 (130 days) in the coastal-tableland region of Alagoas. The experimental design was of randomised blocks, with the treatments comprising six cultivars of different maturity groups and growth habits (M 6210, M 6410, BMX-Potência, AS 3730, M 8349 and BRS-9383). The following were evaluated: plant height, dry matter and leaf area index (LAI). The sigmoidal and pic log-normal logistic models showed a significant statistical fit (p<0.05) to the growth variables and adjusted coefficients of determination (R2adj), with a maximum of 0.994 and 0.990, respectively. The observed values ​​and those estimated by the models showed a high association by the Pearson (r) and Willmott (d) indices, with a low Standard Error of the Estimate (SEE). The BRS-9383 cultivar had the highest observed and estimated growth rates. Under irrigation, the maximum values for plant height ​​were 98.45 and 110.35 cm, with maximum dry matter of 65.88 and 78.70 g, and maximum LAI of 7.68 and 7.60. Under rainfed conditions, the maximum plant height was 62.91 and 72.85 cm, maximum dry matter was 40.0 and 44.91 g, and the maximum LAI was 6.34 and 6.26. The highest agricultural yields under irrigation were 6.19 and 5.90 Mg ha-1 for the AS 3730 and M 8349 cultivars. Under rainfed conditions, the M 6410 and M 8349 cultivars stood out with grain yields of 3.60 and 3 .30 Mg ha-1. Thus, growth models can be used to help analyse growth as a function of days after planting.